2011
DOI: 10.1111/j.1365-2109.2011.03044.x
|View full text |Cite
|
Sign up to set email alerts
|

On the breeding behaviour and reproduction of the freshwater prawn,Macrobrachium rosenbergii(de Man 1879) (Decapoda-Crustacea) under laboratory conditions

Abstract: The giant freshwater prawn, Macrobrachium rosenbergii is one of the most common decapod species, and now getting more attention from the aquaculturists world wide due to its high market demand. It is commercially important because of its size as well as its eating flesh qualities. The breeding behaviour, reproduction and hatching of this species were observed for about 8 months during 2009. Juveniles (0.55 ± 0.177 g total weight and 2.7 ± 0.12 cm, total length) were reared in rounded fibre glass tanks (1.3 m, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…Cavalli, Lavens and Sorgeloos () reported that mature M. rosenbergii females at body weights of 20.0–55.8 g can produce 26,587–74,775 eggs. Analogous result has also been observed by Habashy () who noted 2,050–150,500 eggs for females weighing 4.71–39.1 g.…”
Section: Response Of the Berried Macrobrachium Rosenbergii To Treatmesupporting
confidence: 89%
See 3 more Smart Citations
“…Cavalli, Lavens and Sorgeloos () reported that mature M. rosenbergii females at body weights of 20.0–55.8 g can produce 26,587–74,775 eggs. Analogous result has also been observed by Habashy () who noted 2,050–150,500 eggs for females weighing 4.71–39.1 g.…”
Section: Response Of the Berried Macrobrachium Rosenbergii To Treatmesupporting
confidence: 89%
“…The eggs of M. rosenbergii , in the present study, hatched out within 21 days but the probiotics treatment promoted this process in less time, that is in 19 days (Table ; Figure ). Comparable studies also reported the egg hatching (incubation) time of M. rosenbergii in 19 days at 26–28°C (Ling, ), 20 days at 28°C (Habashy et al., ), or in the range of 18–24 days at about 28°C (Habashy, ). Other performance indicators of M. rosenbergii breeders include number of hatched larvae, fecundity and hatching rate, and these data were particularly encouraging with probiotics than the control group, that is hatched larvae per spawner was 36,302 ± 323 (probiotics) vs. 33,349 ± 198 (control), relative fecundity (eggs g −1 ) was 545 ± 7 vs. 519 ± 9, and hatching rate (%) was 94 ± 1.0 vs. 91 ± 1.1 (Table ).…”
Section: Response Of the Berried Macrobrachium Rosenbergii To Treatmementioning
confidence: 93%
See 2 more Smart Citations
“…Furthermore, the neo-females presented no significant fecundity changes relative to normal females in terms of the average number of eggs/g total body weight. In this respect, the results of the present study for both normal and neofemales were within the range reported by Habashy (2013), who showed a range of 435 to 3849 eggs/g and also within the values presented by Jee and Kok (1991), (1132 ± 484 to 745 ± 487 eggs/g body weight) in mature M. rosenbergii normal females. The brood somatic index (BSI) was very similar in both groups, implying a normal ratio between prawn egg mass to body weight of the neo-females.…”
Section: Comparisons Of Normal Prawn Populations With Rnai-manipulatesupporting
confidence: 86%